FLORA ETNOMEDICINAL DEL CERRO “LA BOTICA”, EMPLEADA POR EL POBLADOR DE CACHICADÁN, SANTIAGO DE CHUCO, PERÚ, 2019. - ALIPIO RODRIGUEZ, Anavely Leslie (2019)
The ancestral knowledge of our ancestors, demonstrates the intelligent use they have made of phytodiversity; and that to this day the Andean-Amazonian and rural communities, especially, have known how to use them; and that over time and for the benefits obtained, they have been practically waiting to be validated by the investigation. This work was oriented to determine the ethnomedicinal flora of the hill “la botica”, used by the people of Cachicadán, Santiago de Chuco, Peru, 2019. 94 semi-structured interviews were applied, following the “snowball” technique, in parallel the collections through botanical explorations, as well as a critical review of the specialized bibliography, reinforcing this information with that obtained by the personal experience of both the researchers and the residents of the district. For each of the species, family data, scientific and common name, part used, disease or disease treated, location in UTM and use value index (IVU) were detailed. 48 species of flora are used ethnobotanically by the people of Cachicadán, distributed in 46 genera and 26 families, of which they stand out for their number of species: Asteraceae (10), Rosaceae (5) and Lamiaceae (3). Being the most important species Desmodium molliculum (Kunth) DC. "pie de perro" (IVU=0.88), Linum usitatissimum L. "linaza" (IVU=0.88), Perezia multiflora (Humb. & Bonpl.) Less. "escorzonera" (IVU= 0.86), Minthostachys mollis (Benth.) Griseb. "muña" (IVU= 0.85), Picrosia longifolia D.Don "chicoria" (IVU= 0.84), Plantago major L. "llantén" (IVU=0.84), Dioscorea moyobambensis R.Knuth "papa semitona" (IVU= 0.82), Eucalyptus globulus Labill. "eucalipto" (IVU= 0.82), Cestrum auriculatum L'Hér. "hierba santa" (IVU= 0.81), Sonchus oleraceus (L.) L. "cerraja" (IVU= 0.80), Prunus serotina Ehrh. "capulí" (IVU=0.80) and Clinopodium pulchellum (Kunth) Govaerts "panizara" (IVU= 0.80).